2011
DOI: 10.1074/jbc.m110.202002
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Adenosine Diphosphate Ribose Activates Ryanodine Receptors, whereas NAADP Activates Two-pore Domain Channels

Abstract: The mechanism by which cyclic adenosine diphosphate ribose (cADPR) and nicotinic acid adenine dinucleotide phosphate (NAADP) mobilize intracellular Ca 2؉ Intracellular Ca 2ϩ signals are initiated by Ca 2ϩ release from intracellular stores, and traditionally, the sarco/endoplasmic reticulum (S/ER) 2 has been considered to be the major releasable store. From this store, Ca 2ϩ may be released through the opening of inositol 1,4,5-trisphosphate receptors (IP 3 Rs) and/or ryanodine receptors (RyRs), the two group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(76 citation statements)
references
References 34 publications
4
70
1
1
Order By: Relevance
“…Changes in intracellular Ca 2ϩ were reported by the fluorescence ratio (F 340 /F 380 ) of the Ca 2ϩ indicator Fura-2. As reported previously (1,18), intracellular dialysis of 10 nM NAADP failed to evoke a significant Ca 2ϩ transient in wild-type HEK293 cells (Fig. 4A, panel i), which express very low levels of TPC1 and TPC2 and do not express TPC3 (1,19).…”
Section: Resultsmentioning
confidence: 48%
“…Changes in intracellular Ca 2ϩ were reported by the fluorescence ratio (F 340 /F 380 ) of the Ca 2ϩ indicator Fura-2. As reported previously (1,18), intracellular dialysis of 10 nM NAADP failed to evoke a significant Ca 2ϩ transient in wild-type HEK293 cells (Fig. 4A, panel i), which express very low levels of TPC1 and TPC2 and do not express TPC3 (1,19).…”
Section: Resultsmentioning
confidence: 48%
“…Next, we proceeded to apply the PAL approach in two other cell types, HEK293 cells and mouse pancreas. Both systems have been used as models for studying NAADP-evoked Ca 2ϩ signals (5,6,9,10,14,29,30). PAL samples from HEK WCL displayed a broadly similar labeling pattern to those observed from SKBR3 cells (Fig.…”
Section: Resultsmentioning
confidence: 92%
“…Supporting evidence derives from gain-and loss-of-function approaches, electrophysiological analyses, and radioligand binding. For example, overexpression of either of the two human TPC isoforms (TPC1 and TPC2) enhanced NAADPevoked Ca 2ϩ responses when assessed by Ca 2ϩ imaging in multiple cell lines (5)(6)(7)(8)(9)(10). Reciprocally, knockdown of endogenous TPC1 ablated NAADP responsiveness (7), and NAADP-activated Ca 2ϩ currents were abolished in pancreatic ␤-cells isolated from a TPC2 knock-out mouse (5).…”
Section: Naadpmentioning
confidence: 97%
“…In HEK293 cells transfected with an islet type RyR, which is a splice variant of the RyR2 gene by alternative splicing of exons 4 and 75, Ca 2+ release was enhanced in the presence of 100 μmol/L cADPR, and the effect could be reversed by preincubating with a cADPR antagonist, 8-bromo-cADPR (8-Br-cADPR) [13] . Similarly, cADPR triggered a marked Ca 2+ transient in HEK293 cells that stably expressed RyR1 and RyR3, and this Ca 2+ transient was abolished by dantrolene, an RyR antagonist [14] . In summary, all these results suggested that RyRs might serve as cADPR receptors (Figure 1).…”
Section: The Structure and Function Of Cadprmentioning
confidence: 99%